Cover Feature: Recent Developments in Azaborinine Chemistry (Eur. J. Inorg. Chem. 38‐39/2017). Issue 38 (4th October 2017) - Bélanger‐Chabot, Guillaume; Braunschweig, Holger; Roy, Dipak Kumar
Abstract : The Cover Feature shows a range of interesting boron‐containing compounds that have emerged over the years. The central focus is on the family of azaborinines, upon which our Microreview in this issue is based. Azaborinines, BN analogues of benzene, come in three forms depending on the relative position of the B and N atoms, as depicted on the central watch face. More information can be found in theMicroreview by H. Braunschweig et al.